Effects of high hydrostatic pressure and thermal processing on bioactive compounds, antioxidant activity, and volatile profile of mulberry juice - Wang, Fan (Food science and technology international = Ciencia y tecnologia de los alimentos internacional, 2017)
The aim of this study was to investigate the effects of high hydrostatic pressure and thermal processing on microbiological quality, bioactive compounds, antioxidant activity, and volatile profile of mulberry juice. High hydrostatic pressure processing at 500 MPa for 10 min reduced the total viable count from 4.38 log cfu/ml to nondetectable level and completely inactivated yeasts and molds in raw mulberry juice, ensuring the microbiological safety as thermal processing at 85 ℃ for 15 min. High hydrostatic pressure processing maintained significantly (p < 0.05) higher contents of total phenolic, total flavonoid and resveratrol, and antioxidant activity of mulberry juice than thermal processing. The main volatile compounds of mulberry juice were aldehydes, alcohols, and ketones. High hydrostatic pressure processing enhanced the volatile compound concentrations of mulberry juice while thermal processing reduced them in comparison with the control. These results suggested that high hydrostatic pressure processing could be an alternative to conventional thermal processing for production of high-quality mulberry juice